Fostering women’s engagement in good agricultural practices within oil palm smallholdings: Evaluating the role of partnerships - Chalil Diana; Barus Riantri; Sukiyono Ketut; Putra Arma; Khaliqi Muhammad; Villano Renato Andrin (Open Agriculture)
Smallholder farmers are critical to Indonesia’s oil palm sector, cultivating more than 40% of the total plantation area. Despite their importance, many smallholders have not adopted Good Agricultural Practices (GAP), often due to resource constraints. Given this context, partnerships are considered essential for enhancing GAP adoption, with women expected to contribute positively as integral members of smallholder groups. However, empirical evidence on the specific impact of such partnerships on women’s roles within smallholder operations is limited. This study, utilizing a structural equation modeling approach with data from 480 smallholder households across four Indonesian oil palm centers, investigates the engagement of women in on-farm tasks, on-farm support, farm administration, and financial management. The analysis reveals that women’s involvement in decision-making remains low, and negatively associated with GAP implementation. Notably, however, partnerships demonstrate a significant positive impact on women’s engagement in farm administration and income management. Additionally, the study confirms the positive effect of partnerships on GAP implementation and further shows an indirect positive correlation between women’s participation and GAP adoption. These results underscore that leveraging strategic partnerships is critical in advancing both women’s roles and promoting the adoption of GAP among oil palm smallholders.